2011
DOI: 10.1039/c1cc11230a
|View full text |Cite
|
Sign up to set email alerts
|

What is the initiation step of the Grubbs-Hoveyda olefinmetathesiscatalyst?

Abstract: Density function theory calculations reveal that the GrubbsHoveyda olefin metathesis pre-catalyst is activated by the formation of a complex in which the incoming alkene substrate and outgoing alkoxy ligand are both clearly associated with the ruthenium centre. The computed energies for reaction are in good agreement with the experimental values, reported here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
118
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(132 citation statements)
references
References 12 publications
14
118
0
Order By: Relevance
“…The interchange mechanism supported by our computational work 17 and also by Plenio's experimental data, 18 is earlier with respect to the Ru⋯O extension, and includes the approach of an alkene molecule towards the Ru centre (EVE in the case of initiation) and some sharing of alkene electron density with the Ru centre. The three types of transition states have different shapes, volumes and polarities so it is not surprising that there is no simple relationship between dielectric constant or E T (30) for either pre-catalyst, and that multi-parameter approaches are required.…”
Section: Dalton Transactions Communicationmentioning
confidence: 52%
“…The interchange mechanism supported by our computational work 17 and also by Plenio's experimental data, 18 is earlier with respect to the Ru⋯O extension, and includes the approach of an alkene molecule towards the Ru centre (EVE in the case of initiation) and some sharing of alkene electron density with the Ru centre. The three types of transition states have different shapes, volumes and polarities so it is not surprising that there is no simple relationship between dielectric constant or E T (30) for either pre-catalyst, and that multi-parameter approaches are required.…”
Section: Dalton Transactions Communicationmentioning
confidence: 52%
“…Notice also that in our previous work [21], the enthalpy for nitrogen interaction with Na-ETS-10 calculated with the same cluster model and DFT approach compared well with the available experimental result while a noticeable underestimation (~7 kJ·mol -1 with the M06-L/6-31++G** approach and ~3 kJ·mol -1 with the M06-L/6-31G** approach) was found in the case of carbon dioxide. Note however that the experimental result for carbon dioxide was determined by the same authors reporting the largest value (-49.7 kJ·mol -1 ) for ethene interaction with Na-ETS-10 [36]. This suggests that the much more negative isosteric heats reported by Shi et al [36] may be due to the presence of other cations than Na + in the Na-ETS-10 sample, which interact strongerthan Na cations with CO 2 and with the double bond in ethene.…”
Section: Adsorption Of C 2 H X and C 3 H X Hydrocarbons In Ets-10mentioning
confidence: 93%
“…Note however that the experimental result for carbon dioxide was determined by the same authors reporting the largest value (-49.7 kJ·mol -1 ) for ethene interaction with Na-ETS-10 [36]. This suggests that the much more negative isosteric heats reported by Shi et al [36] may be due to the presence of other cations than Na + in the Na-ETS-10 sample, which interact strongerthan Na cations with CO 2 and with the double bond in ethene. The verification of this hypothesis needs further experimental work and we hope that the present and previous [21] studies on the interaction of gaseous molecules with Na-ETS-10 can trigger such experiments.…”
Section: Adsorption Of C 2 H X and C 3 H X Hydrocarbons In Ets-10mentioning
confidence: 93%
See 1 more Smart Citation
“…Understanding this part of the mechanism is very important because it is central to understanding the entire catalytic cycle. Despite many theoretical efforts on Grubbs catalysts, to our knowledge, only three works have described the metathesis with Hoveyda-Grubbs catalyst: two of them use a dissociative mechanism [18,19] and the other uses an interchange-associative mechanism [20]. We found that the mechanism of catalysis depends on the size of both the olefin and the Hoveyda ligand.…”
Section: Introductionmentioning
confidence: 94%